PENGARUH TINGKAT PENDIDIKAN DAN MOTIVASI KERJA TERHADAP PARTISIPASI KERJA WANITA DI KOTA TASIKMALAYA - Titin - Patimah; Ai Kusmiati Asyiah (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the influence of education level and work motivation simultaneously or partially on women's work participation in Tasikmalaya City. The research method used in this research is a quantitative research method with survey research using a questionnaire using a Likert scale. This research uses a sampling technique using the Accidental Sampling method. The researchers determined there were 343 samples. The data collection technique is by questionnaire. The data analysis technique using multiple linear regression equations was tested simultaneously using the F test and partially using the t test with SPSS software. The results of this research are that simultaneously the level of education and work motivation have a significant effect on work participation. Furthermore, partially the level of education and work motivation have a significant effect on work participation. Apart from that, the variable that has the greatest influence on work participation between the level of education and work motivation is the level of education.